Estimation of cloud fraction profile in shallow convection using a scanning cloud radar - Oue, Mariko; Kollias, Pavlos; North, Kirk W.; Tatarevic, Aleksandra; Endo, Satoshi; Vogelmann, Andrew M.; Gustafson, William I. (Geophysical research letters, 2016)
Large spatial heterogeneities in shallow convection result in uncertainties in estimations of domain‐averaged cloud fraction profiles (CFP). This issue is addressed by using large eddy simulations of shallow convection over land coupled with a radar simulator. Results indicate that zenith profiling observations are inadequate to provide reliable CFP estimates. Use of scanning cloud radar (SCR), performing a sequence of cross‐wind horizon‐to‐horizon scans, is not straightforward due to the strong dependence of radar sensitivity to target distance. An objective method for estimating domain‐averaged CFP is proposed that uses observed statistics of SCR hydrometeor detection with height to estimate optimum sampling regions. This method shows good agreement with the model CFP. Results indicate that CFP estimates require more than 35 min of SCR scans to converge on the model domain average. The proposed technique is expected to improve our ability to compare model output with cloud radar observations in shallow cumulus cloud conditions. Key Points Shallow convection fields provided by LES coupled with a radar simulator were studied A new objective method of estimating domain‐averaged cloud fraction profiles using scanning cloud radar was proposed Cloud fraction profiles from a single zenith cloud radar are subject to large uncertainties